2019
DOI: 10.1038/s41467-019-12705-5
|View full text |Cite
|
Sign up to set email alerts
|

GWAS of mosaic loss of chromosome Y highlights genetic effects on blood cell differentiation

Abstract: Mosaic loss of chromosome Y (mLOY) is frequently observed in the leukocytes of ageing men. However, the genetic architecture and biological mechanisms underlying mLOY are not fully understood. In a cohort of 95,380 Japanese men, we identify 50 independent genetic markers in 46 loci associated with mLOY at a genome-wide significant level, 35 of which are unreported. Lead markers overlap enhancer marks in hematopoietic stem cells (HSCs, P ≤ 1.0 × 10−6). mLOY genome-wide association study signals exhibit polygeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 49 publications
13
79
1
Order By: Relevance
“…Our query returned eight GWAS traits associated with variants in LD with rs2887399 ( Supplementary Table S3). As expected, the main trait found to be associated with rs2887399 was mosaic loss of chromosome Y (19,20). Another associated trait included neutrophil count (21), which is interesting in light of recent articles on mosaic Y loss indicating changes in blood cell counts, particularly neutrophil counts (20,22).…”
Section: Resultssupporting
confidence: 56%
“…Our query returned eight GWAS traits associated with variants in LD with rs2887399 ( Supplementary Table S3). As expected, the main trait found to be associated with rs2887399 was mosaic loss of chromosome Y (19,20). Another associated trait included neutrophil count (21), which is interesting in light of recent articles on mosaic Y loss indicating changes in blood cell counts, particularly neutrophil counts (20,22).…”
Section: Resultssupporting
confidence: 56%
“…Their analysis was also a univariable statistical test which did not take into account potential confounding by other factors. A recently published study on 57, 987 men in Biobank Japan also reported associations among mLOY, increased thrombocyte and leukocyte counts 64 . While the authors did not find statistically significant negative associations between erythrocyte counts and continuous mLRR in univariable models, effect estimates indicate men with mLOY trended toward a decreased erythrocyte count.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, large genome-wide association studies enrolling >200,000 men in the UK Biobank demonstrated association of germline single nucleotide polymorphisms (SNP) of 156 autosomal loci as well as differential methylation of various genes with LOY 4,[25][26][27] . Whether any of the LOYassociated SNPs or epigenetic changes contribute to hematological neoplasia risk is unclear.…”
Section: Introductionmentioning
confidence: 99%